Priority Setting for Biotechnology - The Kenya/DGIS Experience - Olembo, N. K.; Wafula, J. S.; Wekundah, J. M. (International Service for National Agricultural Research, 2001)
In the past Kenya has not been a major food-deficit country, but because of the current high population growth coupled with the shortage of arable land, an imbalance has emerged in the relationship between the national supply of food and demand. Severe shortages in the main foodstuffs have been frequently experienced over the last decade leading to significant dependence on imports. With the country's population now estimated to be 24.4 million and increasing at the rate of 3.34 percent per year, the main challenge is to provide adequate food to meet the demand, which is expected to increase four-fold in the next decade and beyond.